International Congress for the study of the principles of a durable peace, Berne, 1916. Article 5 of the minimum program - Raeburn White, Thomas; Central Organisation for a durable Peace (The Hague : Nijhoff, 1916)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: vredesinitiatieven; Wereldoorlog 1